Uji Aktivitas Antioksidan & Inhibitor α-Glukosidase Bakteri Endofit Daun Jagung (Zea mays L.): Antioxidant and α-Glukosidase Inhibitory Activities of Corn Leaf Endophytic Bacteria (Zea mays L.) - Putri Nadia Utami; Muhammad Yunus; Edy Fachrial (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2026)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia and closely associated with oxidative stress. The development of natural agents with antioxidant properties and α-glucosidase inhibitory activity is considered a promising approach for controlling blood glucose levels. This study aimed to evaluate the antioxidant activity and α-glucosidase inhibitory potential of endophytic bacteria isolated from corn leaves (Zea mays L.). This study was conducted in vitro through the isolation of endophytic bacteria, followed by macroscopic and microscopic characterization using Gram staining, catalase testing, antioxidant activity evaluation using the DPPH method, and α-glucosidase inhibition assays employing p-nitrophenyl- α-D-glucopyranosidase as the substrate. The results showed that ten endophytic bacterial isolates had diverse morphological characteristics, with Gram staining and catalase test results indicating variations in physiological properties between isolates. All isolates showed antioxidant activity with inhibition percentages ranging from 57.4%–76.8%. Isolate P7 showed the highest antioxidant activity and α-glucosidase enzyme inhibition activity of 97.67%, higher than the positive control acarbose.These findings indicate that corn leaf endophytic bacteria, particularly isolate P7, have potential as a natural source of bioactive with antioxidant and antidiabetic properties through the inhibition of α-glucosidase.